SAFETY EVALUATION OF A LYOPHILIZED PLATELET DERIVED HEMOSTATIC PRODUCT - Barroso, Jeffrey (Transfusion, 2018)
BACKGROUND: Hemorrhage causes significant morbidity and mortality in persons under 65. A lyophilized platelet-derived hemostatic agent (Thrombosomes) demonstrated hemostatic efficacy in animal models. We report the results of the first safety trial of autologous Thrombosomes given to normal subjects. STUDY DESIGN AND METHODS: Ten subjects received autologous Thrombosomes prepared from their apheresis platelets and 5 control subjects received a buffer solution. There were 5 Cohorts, 3 subjects/Cohort (2 Thrombosomes, 1 Control). Doses escalated from 1/1,000 to 1/10 of a proposed efficacious dose. Cohorts 4 and 5 received the highest dose, but, in Cohort 5, ½ the dose was infused two hours apart. Cohorts 1–3 were monitored for 42 days, Cohorts 4–5 for 60 days using hematology, coagulation and chemistry assays, and antibody testing. RESULTS: There were no serious adverse events (SAEs) and no subject withdrawals. There were 8 treatment related adverse events (TRAEs) in 5/15 subjects (33%) [4 Thrombosomes (40%), 1 control]. Three of 4 subjects receiving the highest doses had TRAEs. One had elevated D-dimer, Prothrombin Fragment 1+2, and WBC (subject had concurrent upper respiratory infection), one had T-wave inversions in pre-cordial leads V2 and V3 without elevated Troponin or symptoms, and one had a platelet autoantibody without change in platelet count. All subjects TRAEs resolved by day 21. CONCLUSION: As there were no SAEs in this small study. Thrombosomes were considered safe at the doses assessed. Future, larger trials will be needed to further assess safety and efficacy.